Fluoroelastomers handbook : the definitive user's guide and databook - Moore, Albert L. (PDL handbook series., 2006)
Fluoroelastomers Handbook: The Definitive User's Guide and Databook is a comprehensive reference on fluoroelastomer chemistry, processing technology, and applications. This is a must-have reference for materials scientists and engineers in the automotive, aerospace, chemical, chemical process, and power generation industries. Fluoroelastomers meet rigorous performance requirements in harsh environments, enhancing reliability, safety, and environmental friendliness. Fluoroelastomers are growing as products of choice for critical components such as O-rings, hoses, and seals in hostile fluid and temperature conditions. The first part of this book is an overview of fluorocarbon elastomers, including descriptions of the nature of fluoroelastomers, properties of various compositions, developmental history, and major uses. The second part provides more details of fluoroelastomer technology, including monomer properties and synthesis, polymerization and production processes, cure systems, and processing methods. The third and last part covers fluid resistance of various fluoroelastomer families, major applications of fluoroelastomers, and safety and disposal.